Artificial Intelligence dan Inovasi Layanan Perpustakaan Perguruan Tinggi: Systematic Literature Review - Yeni Fitria Nurahman; Anggriawan Kristanto; Afiyatul Fatimah (Media Informasi, 2026)
The development of artificial intelligence (AI) has opened significant opportunities for transforming services in academic libraries. In addition to improving librarians’ operational efficiency through service automation, AI enhances user engagement by enabling more personalized, adaptive, and innovative service models. These developments indicate a growing shift in how academic libraries design and deliver information services. This article presents a systematic literature review (SLR) to examine research trends, identify forms of innovation, and analyze the impact of AI implementation in academic library services. The study followed established SLR procedures, including identification, screening, and thematic analysis of scholarly articles indexed in Google Scholar, with a publication range from 2023 to 2025. The review addressed three primary research questions, first what are the prevailing trends in research on AI implementation in academic libraries; second what types of service innovations have emerged; and last how does AI influence information access, service efficiency, and user experience? The findings show that AI has been applied in various domains, including information recommendation systems, reference service chatbots, catalog automation, and user behavior analytics. Despite these advancements, several challenges remain, particularly regarding librarians’ digital competencies, ethical considerations, and the integration of AI technologies with institutional academic needs. Overall, the findings position AI as an important catalyst for innovation in academic libraries while highlighting the need for further research on its broader social, cultural, and ethical implication